Motivasi Peternak Sapi Dalam Adopsi Inovasi Inseminasi Buatan (IB): Studi Kasus Municipio Bobonaro Dan Municipio Covalima, Timor Leste - Urbano Maria Tilman Suri; Joni Murti Mulyo Aji; Lenny Widjayanthi (JSEP (Journal of Social and Agricultural Economics), 2022)
Since 2016, cattle farmers in Municipio Bobonaro and Municipio Covalima have carried out IB for their livestock, although there are still some farmers who do not or cannot do due to lack of access. This is related to the motivation of farmers with artificial insemination programs. The aim of our study was to determine the level of motivation regarding the cattle artificial insemination (IB) program, the level of adoption of IB program and to analyze the relationship between farmer characteristics and motivation regarding the IB program and the level of adoption of IB program innovation in cattle business in the municipality of Bobonaro and Covalima municipality. This research was conducted using a survey method approach and was carried out in the Municipio Bobonaro and Municipio Covalima. A total of 44 farmers participated in the program were included in the sample using a census strategy. Chi squared correlations, Spearman Rho, and quantitative descriptive analysis were used to analyze the data. The results showed that the level of motivation of farmers regarding the artificial insemination program included high criteria, while the level of innovation adoption of artificial insemination programs included medium criteria. Experience of raising cattle had a significant relationship with the motivation of farmers.